ATENCIÓN AL ADULTO MAYOR EN LAS COMUNIDADES ANDINAS - Hallasi Roselló y Cols., Dilma Diany (2019)
The greater adult is losing the use of some of his faculties. To certain people the oldness produces rejection to him because it is dealing with individuals that apparently hinder due to the difficulty in walking, hearing and to remember; in addition they are more ready to the diseases. If this happens in the cities, in the Andean zone the situation is more dramatic. The investigation consisted of interviewing greater adults of the Andean communities to expose its situation with the aim that the people in charge can act in benefit of those citizens. They live single or with their pair if they have her, the children have emigrated, the aid is enough due to the distance and the lack of suitable routes of communication, practically lack everything, the poverty is extreme, live in huts, their utensils are artisan old and covered with dust by the little use that they give them. They are fed basically on maize, barley and other cereals, almost nothing of proteins. The only medical aid that receives is of the Brigade of Health. By the few  bmedicines, they value the affection whereupon they are treated, the affection is what they more wish to receive. In its solitude they live on its memories. Most human than they wish is the respect of its resemblances reason why they try to participate in the communal actions to maintain their self-esteem.